English as a Lingua Franca Awareness of the Pre-service English Teachers in Assessing Students’ Speaking Assignment - Situmorang, Komilie; Nugroho, Dwi Yulianto; Pramusita, Santa Maya; Sihombing, Michael Recard (OKARA: Jurnal Bahasa dan Sastra, 2023)
The permeating use of English promotes a contact language among people from multicultural backgrounds called English as a Lingua Franca (ELF). Pre-service English teachers going to the teaching practice thus need to be aware of ELF trends to engage with their students in the classroom. This study seeks to explore the ELF awareness of the pre-service English teachers in assessing the students’ speaking assessment. Twenty pre-service teachers from three geographically different universities were recruited. They were asked to establish the speaking rubrics assessment based on the given video and were invited to Forum Group Discussion (FGD) for their underlying reasons for scoring. The results indicated that University A developed ELF awareness as they demonstrated open-mindedness, tolerance, less value on errors, and emphasis on intelligibility both personally and professionally. Meanwhile, Universities B and C openly state that Native speakersâ€™ English is the only proper English, and any other use beyond it is a defect. The discussion suggests that the different geographical locations may cause different exposures to speakers of English. The study suggests that pre-service English teachers actively explore the ongoing trend in English Language Teaching with the Faculty of Education to provide continuous support in the process.